Eurozone crisis : will reforms be enough? - Rana, Pradumna B. (2012)
The Economic and Monetary Union launched in Europe in 1999, was an experiment amongst countries with diverse economic structures. A number of reforms have since been initiated to address the flaws in its design. Will these reforms be enough to save the euro?